(untitled) (AYUSHDHARA, 2019)
Atisara is essentially a vitiation of Abdhatu though it is manifested in the Gastro Intestinal tract. This is a psychosomatic condition. The mental factor plays a major role in the pathogenesis of the disease. This is supported by various dietetic factors and environmental conditions. India is a developing country. It has not reached to that level of advanced countries where the water supplies the drainage systems and health education have attained the ideal level of health care. A study of ‘Ayurvedic Herbal compound’ has been carried out in 25 cases of ‘Atisara’ with Madhyama Shrenee of Abdhatukshaya (moderate degree of dehydration) with following specific aims and objectives. The Ayurvedic Herbal Compound - Tab ‘H’ contains study the efficacy of herbal combination Kutaja + Bilva + Shunthi + Vacha + Vidanga. After studding pathological findings in the stools before and after treatment of Tab H it is observed that after Tab H treatment the number of pus cells in the stools has effectively decreased from 68% to 12% of the total number of patients. The number of mucus cells in the stools has markedly decreased from 24% to 4% of the total number of the patients Cysts of Entamoeba histolytica has disappeared from 36% to 12% of the total number of the patients. Thus it is conclude that the Tab. H has shown efficacy in pathological cure in the disease.